Principal Strategies for Enhancing Teacher Professional Competence: A Systematic Literature Review on Instructional Leadership, Academic Supervision, and Continuous Professional Development - Nurani Nurani; Trian Hermawan; Muhammad Akmansyah; Zulhanan Zulhanan; Fachrul Ghazi (Assyfa Journal of Islamic Studies, 2026)
Teacher professional competence is a prerequisite for instructional quality, as it relates to mastery of subject matter, the ability to develop knowledge, the use of technology, professional reflection, and the capacity to translate curriculum goals into meaningful learning experiences. This article aims to synthesize principal strategies for enhancing teacher professional competence through a Systematic Literature Review (SLR). The review adapts the PRISMA 2020 guidelines and searches literature across SINTA/Garuda, Google Scholar, DOAJ, ERIC, ScienceDirect, SAGE, Emerald, SpringerOpen, and reputable international journal platforms. Inclusion criteria cover articles published between 2016 and 2026 that focus on principal leadership, teacher professional competence, academic supervision, professional learning communities, and continuous professional development. Exclusion criteria include articles without adequate bibliographic access, those irrelevant to school-level contexts, and those lacking strategic implications for teacher competence improvement. The synthesis identifies six clusters of principal strategies: vision-based instructional leadership; clinical-collaborative academic supervision; needs-based continuous professional development; teacher learning communities; data-driven and digital technology utilization; and the internalization of Islamic values such as amanah (trustworthiness), ihsan (excellence), itqan (precision), syura (consultation), and taawun (mutual cooperation). This article offers the DASA-PKB strategic cycle model comprising competence diagnosis, learning vision, supervision and coaching, learning community action, digital resource strengthening, quality control, and sustainable professional culture. The article’s contribution lies in integrating SINTA 1-3 and Scopus Q1-Q3 literature with Islamic normative foundations, thereby serving as a conceptual basis for school policy development and further research.